THE ROADIAN STAGE OF THE PERMIAN AND PROBLEMS OF ITS GLOBAL CORRELATION - Leven E.Ya.; Bogoslovskaya M.F. (My University, 2006)
Ammonoids, conodonts, and fusulinids from the type sections of the Roadian and contiguous stages in western Texas and adjacent areas are analyzed and partially revised. Four successive Roadian ammonoid assemblages are distinguished and correlated with conodont zones; data on their distribution are presented. Based on the results obtained, the Roadian Stage is identified in the Boreal and Tethyan regions. Boundaries of the Roadian Stage defined accurately in the type sections of Texas are hardly recognizable elsewhere. Recognition of the upper boundary is especially difficult. Occurrence of Roadian fossils means that deposits of this age are present in a sequence, but they cannot be differentiated from underlying and overlying beds. Like in the type area, the stage lower boundary based on conodonts is above the level of significant changes in marine biota within the Boreal and Tethyan realms as well. The upper boundary is not marked by noticeable biotic events either. Correlation of the Roadian deposits is imprecise because their boundaries are formally established using distribution of relatively rare conodonts.
Keywords: Permian; Paleozoic::Permian; Палеозой::Пермская